2019
DOI: 10.1080/14786419.2019.1616726
|View full text |Cite
|
Sign up to set email alerts
|

Capsulated essential oil in gel spheres for the protection of cellulosic cultural heritage

Abstract: In this paper we present a possible application of cinnamon essential oil to be encapsulated into gel drops of psyllium and of psyllium-alginate mixtures and to be released by the beads. It could act as green biocide for the protection of antique books, old documents and, generally, of any cellulosic material (paper, wood, textiles) object of cultural interest from biological attack. The components of the cinnamon essential oil, released by alginate, psyllium-alginate and purified psyllium-alginate beads, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…EOs' roles as antimicrobial agents have been tested on paper documents [13][14][15], historical textiles [16], wooden and stone artefacts [17,18], and also on objects of large dimensions [19]. Elsayed and Shabana [20] evaluated the effect of some EOs on fungal infestation on simulated painting models.…”
Section: Introductionmentioning
confidence: 99%
“…EOs' roles as antimicrobial agents have been tested on paper documents [13][14][15], historical textiles [16], wooden and stone artefacts [17,18], and also on objects of large dimensions [19]. Elsayed and Shabana [20] evaluated the effect of some EOs on fungal infestation on simulated painting models.…”
Section: Introductionmentioning
confidence: 99%
“…C. zeylanicum EO has been poorly studied in restoration. In particular, two types of applications were tested: the first was through the nebulization of this EO to preserve ancient textile fibers, while the second exploited the effectiveness of the EO encapsulated in psylliumalginate beads [21,22]. Considering the antimicrobial efficacy already established in the literature of C. zeylanicum EO and its vapors, we decided to study the activity of this EO in association with the C. aurantium var amara Hy already known as an anti-fungal treatment for cultural heritage [10].…”
Section: Discussionmentioning
confidence: 99%
“…The study showed the bactericidal and fungicidal activity of vapours of C. zeylanicum EO in disinfecting textiles without altering their chemical-physical characteristics. In a recent work, Campanella et al [19] showed the potential use of C. zeylanicum EO when encapsulated in psyllium-alginate beads for applications on paper works [19]. However, the Hy of C. aurantium var.…”
Section: Discussionmentioning
confidence: 99%
“…The former are extremely concentrated hydrophobic natural products with an important antimicrobial activity, and that cannot be used pure because they are potentially toxic. Several research groups have tested the antimicrobial activity of EOs especially in the restoration of marble artworks, while studies of their applications on other types of cultural heritage such as paper, textile, or painting artworks are limited [12][13][14][15][16][17][18][19][20][21][22]. Whereas, the latter (very cheap products of distillation) are extremely diluted hydrophilic mixtures with lower microbicidal activity in exchange for a higher versatility and safety.…”
Section: Introductionmentioning
confidence: 99%